Treatment Response Distinguishes Persistent Type of Methamphetamine Psychosis From Schizophrenia Spectrum Disorder Among Inmates at Japanese Medical Prison - Sekiguchi, Yosuke; Okada, Takayuki; Okumura, Yusuke (Frontiers in Psychiatry, 2021)
Introduction: Persistent methamphetamine-associated psychosis (pMAP) is a disorder similar to schizophrenia, so much so that the differences in clinical symptoms and treatment response between the two remain unknown. In this study, we compared the features of pMAP with those of schizophrenia spectrum disorders (SSD). Materials and Methods: This was a retrospective quasi-experimental case-control study of inmates in a medical prison. The behavioral problems, clinical symptoms, and chlorpromazine (CP)-equivalent doses of 24 patients with pMAP and 27 with SSD were compared. Results: Patients in the pMAP group were hospitalized for fewer days than those in the SSD group (281.5 vs. 509.5; p=.012), but there were no other significant group differences in behavioral problems or clinical symptoms. The pMAP group received fewer antipsychotics in CP-equivalent doses than the SSD group at 4, 8, and 12 weeks after admission and at the time of discharge (p=.018, .001, .007, and .023, respectively). The number of CP-equivalent doses in the SSD group tended to increase after admission, but not in the pMAP group. Discussion: These findings suggest that differentiation between pMAP and SSD based on behavior and symptoms alone may be difficult, and that patients with pMAP may respond better to treatment with a lower dose of antipsychotic medication than those with SSD. Further confirmatory studies are warranted.